Well, from what I can tell, we just have to combine like terms, meaning that all of the terms that have the same variables can be combined:
F = (ABC + ABC) + A'B
F = 2ABC + A'B
If that's not what you meant, or if you have questions, feel free to let me know! :)
A) The new dimensions would be 32cm by 12cm.
B) This is an enlargement.
To find the new dimensions, multiply the original dimensions by the scale factor. 8*4=32 and 3*4=12.
This is an enlargement because the copy is larger than the original.
FIRST section: x^2-3x+2 = x^2-x-2x+2=(x^2-x) -2x+2 = (x^2-x) -2(x-a million) = x(x-a million) -2(x-a million) = (x-2)(x-a million) 2nd section: x^-4 = x^2- 2^2 = (x-2)(x+2) So now your equation looks like this: FIRST section / 2nd section or (x-2)(x-a million) / (x-2)(x+2) and this comes out at (x-a million) / (x+2), so the respond is B.
Answer:
7x^2+5x
Step-by-step explanation:
Given
Polynomial 1: 9x^2+8x
Polynomial 2: 2x^2+3x
We have to find subtraction of both
So,
9x^2+8x - (2x^2+3x)
First of all the brackets will be eliminated by multilying the minus sign
9x^2+8x-2x^2-3x
The terms with same power of variable will be written together
9x^2-2x^2+8x-3x
=7x^2+5x ..
Answer:
98.6°F (37°C) the highest Six's thermometer that All I know sry
Step-by-step explanation: